Boron-doped ultrananocrystalline diamond synthesized with an H-rich/Ar-lean gas system. (April 2015) - Zeng, Hongjun; Konicek, Andrew R.; Moldovan, Nicolaie; Mangolini, Filippo; Jacobs, Tevis; Wylie, Ian; Arumugam, Prabhu U.; Siddiqui, Shabnam; Carpick, Robert W.; Carlisle, John A.
Abstract: This paper reports the recent development and applications of conductive boron-doped ultrananocrystalline diamond (BD-UNCD). The authors have determined that BD-UNCD can be synthesized with an H-rich gaseous chemistry and a high CH4 /H2 ratio, which is opposite to previously reported methods with Ar-rich or H-rich gas compositions but utilizing very low CH4 /H2 ratios. The BD-UNCD reported here has a resistivity as low as 0.01 ohm cm, with low roughness (<10 nm) and a wide deposition temperature range (450–850 °C). The properties of this BD-UNCD were studied systematically using resistivity characterization, scanning and transmission electron microscopy, Raman spectroscopy, and roughness measurements. Near Edge X-ray Absorption Fine Structure (NEXAFS) spectroscopy confirms that up to 97% of the UNCD is deposited as sp 3 carbon. These various measurements also reveal additional special properties for this material, such as an "M" shape Raman signature, line-granular nano-cluster texture and high CH bond surface content. A hypothesis is provided to explain why this new deposition strategy, with H-rich/Ar-lean gas chemistry and a high CH4 /H2 ratio, is able to produce high sp 3 -content and/or heavily doped UNCD. In addition, a few emerging applications of BD-UNCD in the field of atomic force microscopy, electrochemistry and biosensing are reviewed here.